2021
DOI: 10.1038/s41431-021-00994-8
|View full text |Cite
|
Sign up to set email alerts
|

Using deep-neural-network-driven facial recognition to identify distinct Kabuki syndrome 1 and 2 gestalt

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The typical KS face includes long palpebral fissures associated with eversion of the lateral third of the lower eyelid; long and heavy lashes giving the impression of made-up eyes; broad, arched and interrupted eyebrows; broad, depressed nasal tip; and prominent, cupped ears 1 , 2 , 4 . Extra-facial features include mild to moderate intellectual disability, visceral malformations, skeletal dysplasia and immunological manifestations 5 . KS has been described in all ethnic groups 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical KS face includes long palpebral fissures associated with eversion of the lateral third of the lower eyelid; long and heavy lashes giving the impression of made-up eyes; broad, arched and interrupted eyebrows; broad, depressed nasal tip; and prominent, cupped ears 1 , 2 , 4 . Extra-facial features include mild to moderate intellectual disability, visceral malformations, skeletal dysplasia and immunological manifestations 5 . KS has been described in all ethnic groups 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The field of dysmorphology has been changed by these new methods, under the name of Next Generation Phenotyping (NGP) 18 . Publications comparing human performances to NGP are flourishing 19 22 , and some suggest that digital tools do it better than human experts in terms of diagnosis: Dudding-Byth et al 23 showed a better performance of NGP compared to clinicians in a group of ten genetic syndromes, not including KS; Rouxel et al 5 compared the performance of the DeepGestalt technology 18 using the Face2Gene online tool (FDNA Inc. Boston, MA, USA) to the performances of clinicians trained in the recognition of KS1 and KS2.…”
Section: Introductionmentioning
confidence: 99%
“…Once it exists, the spatial location and extent of each instance are returned [5]. Many approaches have been proposed to detect faces, parts of faces, and features of faces [6][7][8][9][10][11][12]. A novel reverse engineering approach is used to detect which facial features are critical for users' identity and to use these features as eye prints [6].…”
Section: -Introductionmentioning
confidence: 99%
“…Specifically, these systems have given significant upgrades in object identification. Profound learning has changed a wide scope of the AI era, from picture order and video handling to discourse acknowledgment and common language understanding [9,10].…”
Section: -Introductionmentioning
confidence: 99%
“…Telemedicine to access clinical genomics advice is one route to overcome geographical barriers. Rouxel et al report a facial recognition method to aid the differential diagnosis of Kabuki syndrome [18]. Technological advances continue to improve genomic diagnostics.…”
mentioning
confidence: 99%